2014
DOI: 10.1371/journal.pone.0091423
|View full text |Cite
|
Sign up to set email alerts
|

2DEGs at Perovskite Interfaces between KTaO3 or KNbO3 and Stannates

Abstract: We report density functional studies of electron rich interfaces between KTaO3 or KNbO3 and CaSnO3 or ZnSnO3 and in particular the nature of the interfacial electron gasses that can be formed. We find that depending on the details these may occur on either the transition metal or stannate sides of the interface and in the later case can be shifted away from the interface by ferroelectricity. We also present calculations for bulk KNbO3, KTaO3, CaSnO3, BaSnO3 and ZnSnO3, showing the different transport and optic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

6
32
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 68 publications
6
32
1
Order By: Relevance
“…13,16 The fundamental understanding of BSO has also improved, including its electronic structure in bulk, 10,[17][18][19][20][21][22] as well as its phonon spectrum, 17 optical properties, 10,11,17,[20][21][22]26 scattering mechanisms, 10,[13][14][15]27 defects, 28 and thermal stability. 9 It is understood that the conduction band is derived from Sn 5s states 10,[17][18][19][20][21][22][23][24][25] and progress is being made in identifying mobility-limiting mechanisms in crystals [9][10][11] and films. 9,10,[13][14][15]27 There remain a number of unresolved issues, however, including the optimal choice of dopant ion and site 13 and the relative importance of phonon, 11,17 neutral impurity, ionized impurity, 9,…”
mentioning
confidence: 99%
“…13,16 The fundamental understanding of BSO has also improved, including its electronic structure in bulk, 10,[17][18][19][20][21][22] as well as its phonon spectrum, 17 optical properties, 10,11,17,[20][21][22]26 scattering mechanisms, 10,[13][14][15]27 defects, 28 and thermal stability. 9 It is understood that the conduction band is derived from Sn 5s states 10,[17][18][19][20][21][22][23][24][25] and progress is being made in identifying mobility-limiting mechanisms in crystals [9][10][11] and films. 9,10,[13][14][15]27 There remain a number of unresolved issues, however, including the optimal choice of dopant ion and site 13 and the relative importance of phonon, 11,17 neutral impurity, ionized impurity, 9,…”
mentioning
confidence: 99%
“…18 As mentioned, BaSnO 3 shows considerable promise as a new n-type transparent conducting oxide (TCO). This material, which has a simple s-band electronic structure, 17,[19][20][21][22][23][24] is dopable to a highly conductive state using Sb or La, 25 and has been developed as a high performance TCO. [6][7][8][9][10][11][12] The related compounds, CaSnO 3 and SrSnO 3 , occur in distorted orthorhombic perovskite structures, 26 while ZnSnO 3 occurs in a ferroelectric LiNbO 3 type structure.…”
mentioning
confidence: 99%
“…[4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] Importantly, recent studies of high mobility La doped BaSnO 3 transparent conducting films show transport properties that are still dominated by extrinsic defects, specifically dislocations. 12,18,19 The implication is that there remains considerable room for even better conductivity with improvements in film perfection.…”
mentioning
confidence: 99%
“…12,18,19 The implication is that there remains considerable room for even better conductivity with improvements in film perfection. Recent studies suggested that n-type BaSnO 3 may have substantial tunability, e.g., in the band gap via alloying and strain, [14][15][16][17] but applications of strain tuning of BaSnO 3 have yet to be demonstrated. Here, we show that it is possible to tailor the spectral transmission of BaSnO 3 by a dimensional reduction strategy.…”
mentioning
confidence: 99%
See 1 more Smart Citation